(untitled) (Journal Of Educational and Psychological Researches, 2022)
Mercifulness is a trait of civilization, humanity, and a moral value in society, because it has an impact on social life and its role in spreading interdependence, joint liability, and solidarity among people. Mercifulness means spreading mercy, synergy, sympathy, and cooperation. Generally, a society that enjoys strong ties tends to have a kind of stability and development, as well as, is able to face the economic, political, and security crises. Conversely, a weak society leads to weak social cohesion and weak community infrastructure that is more vulnerable to social, economic, and political instability. Thus, this is the aim of the research that has used a social survey method applied to a sample of respondents who have reached (300) respondents distributed on both sides of Karkh and Rusafa of Baghdad. The vast majority of respondents believe that sectarianism is the most dangerous phenomenon that Iraq witnessed after 2003. Hence, the research emphasized fighting extremist and extremism ideology by encouraging and strengthening kinship ties and family ties as it contributes to strengthening social construction and increases social cohesion.